qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$x = 3 ^ { \frac { 1 } { 3 } } + 3 ^ { - \frac { 1 } { 3 } }$
$x = 3 ^{ \frac{ 1 }{ 3 } } +3 ^{ - \frac{ 1 }{ 3 } }$
$x = \dfrac { 3 \sqrt[ 3 ]{ 3 } + \sqrt[ 3 ]{ 9 } } { 3 }$
$ $ Solve a solution to $ x$
$x = \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ \frac { 1 } { 3 } } } + 3 ^ { - \frac { 1 } { 3 } }$
$ $ Calculate power $ $
$x = \sqrt[ \color{#FF6800}{ 3 } ]{ \color{#FF6800}{ 3 } } + 3 ^ { - \frac { 1 } { 3 } }$
$x = \sqrt[ 3 ]{ 3 } + 3 ^ { \color{#FF6800}{ - } \color{#FF6800}{ \frac { 1 } { 3 } } }$
$ $ If the exponent is negative, change it to a fraction $ $
$x = \sqrt[ 3 ]{ 3 } + \dfrac { 1 } { 3 ^ { \frac { 1 } { 3 } } }$
$x = \sqrt[ 3 ]{ 3 } + \dfrac { 1 } { \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ \frac { 1 } { 3 } } } }$
$ $ Calculate power $ $
$x = \sqrt[ 3 ]{ 3 } + \dfrac { 1 } { \sqrt[ \color{#FF6800}{ 3 } ]{ \color{#FF6800}{ 3 } } }$
$x = \sqrt[ 3 ]{ 3 } + \color{#FF6800}{ \dfrac { 1 } { \sqrt[ 3 ]{ 3 } } }$
$ $ Calculate the expression $ $
$x = \sqrt[ 3 ]{ 3 } + \color{#FF6800}{ \dfrac { \left ( \sqrt[ 3 ]{ 3 } \right ) ^ { 2 } } { 3 } }$
$x = \sqrt[ 3 ]{ 3 } + \dfrac { \left ( \sqrt[ \color{#FF6800}{ 3 } ]{ \color{#FF6800}{ 3 } } \right ) ^ { \color{#FF6800}{ 2 } } } { 3 }$
$ $ Calculate power $ $
$x = \sqrt[ 3 ]{ 3 } + \dfrac { \sqrt[ \color{#FF6800}{ 3 } ]{ \color{#FF6800}{ 9 } } } { 3 }$
$x = \sqrt[ \color{#FF6800}{ 3 } ]{ \color{#FF6800}{ 3 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { \sqrt[ 3 ]{ 9 } } { 3 } }$
$ $ Find the sum of the fractions $ $
$x = \color{#FF6800}{ \dfrac { 3 \sqrt[ 3 ]{ 3 } + \sqrt[ 3 ]{ 9 } } { 3 } }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo